Bis(2-hydroxyethyl)ammonium 2-bromophenolate - Padayachy, Kamentheren (International Union of Crystallography, 2012)
In the crystal structure of the 1:1 title salt, C(4)H(12)NO(2) (+)·C(6)H(4)BrO(−), hydrogen-bonding interactions originate from the ammonium cation, which adopts a syn conformation. A gauche relationship between the C—O and C—N bonds of the 2-hydroxyethyl fragments also facilitates O—H⋯O interactions of bis(2-hydroxyethyl)ammonium cation chains to phenolate O atoms. The resulting double-ion chains along [100] are further linked by N—H⋯O interactions, forming chains parallel to [110].